Representatives of the public? Public opinion and interest group activity. (4th November 2013) - Rasmussen, Anne; Carroll, Brendan J.; Lowery, David
Abstract Although scholars have long speculated about how organised interests link the public to decision makers, there has actually been little empirical research on this important element of democratic theory. This important gap in the literature is addressed in this article by examining, in addition to other supply‐side and demand‐side factors, whether groups mobilise on issues in policy areas that are regarded as salient by the public. Based on an analysis of 4, 501 contributions in 142 European Commission online consultations, it is found that organised interests potentially can act as a transmission belt between the public and decision makers. Although the results vary to some degree by issues, higher rates of mobilisation are found on those issues that fall within policy areas that are regarded as salient by the general public and those with consequences for budgetary spending.